OP0234 MBS2320, A NOVEL SELECTIVE MODULATOR OF IMMUNE METABOLISM, IN PATIENTS WITH SEVERE RHEUMATOID ARTHRITIS: SAFETY, TOLERABILITY AND EFFICACY RESULTS OF A PHASE 2 STUDY. (2nd June 2020) - Patel, L.; Skillern, L.; Foster, M.; Gray, A.; Leff, R.; Williams, S.
Abstract : Background: Despite the availability of several treatment options for Rheumatoid Arthritis (RA), many patients are classed as 'non-responders' who show little or no improvement. Hence, there remains a need for new therapies with a differentiated mechanism of action, to be used alone or in combination. MBS2320 is a selective modulator of immune metabolism displaying distinctive dual pharmacology: strong anti-inflammatory activity as well as a broader spectrum of osteoprotection than TNFα inhibition in preclinical models 1 . Objectives: To evaluate the safety, tolerability and efficacy of MBS2320 in patients receiving a stable dose of methotrexate (MTX). Methods: Patients with active RA on a stable dose of MTX were randomised 2:1 to receive MBS2320 (80mg) or matching placebo once daily for 4 weeks. Subject to a satisfactory safety and tolerability assessment, patients were escalated to a dose of 120 mg qd or remained on 80 mg qd for a further 8 weeks. Safety, efficacy, pharmacokinetics and pharmacodynamics were evaluated. Results: 121 patients were randomised (Safety analysis set) to MBS2320 or matching placebo and 96 completed the study. Sixteen subjects were excluded from the efficacy analysis set due to evidence of poor compliance or absence of efficacy evaluations. Enrolled patients were mostly female (86.8%), white and with a mean (range) age at baseline (BL) of 52 (19-69) years. The study population had hard-to-treat, severe, active and erosive disease as indicated by high BL DAS28-CRP and DAS28-ESR, low Week-12 placebo ACR50 and DAS28-CRP responder rates (2.5% and 5% respectively) and a low ratio of synovitis-to-erosion volume despite treatment with DMARD(s). There were no serious treatment emergent adverse events (TEAEs). 15 patients (19%) randomised to MBS2320 withdrew due to TEAEs, predominantly of nausea. TEAEs were typically reported soon after dosing, were mostly mild in severity and resolved without treatment. Onset of TEAEs reduced as the study proceeded. Gastrointestinal disorders were the most frequently reported TEAEs (all causalities) with a higher incidence in patients receiving MBS2320 (68.8%) than placebo (14.6%). Nausea was most frequently reported during Week 1 (27.3% patients). Asthenia and/or fatigue was reported more frequently in the MBS2320 treatment group (23.8% patients) than with placebo (7.3% patients), with the majority being considered related to study drug. Infections were more frequently reported by patients receiving placebo (22.0%) than those receiving MBS2320 (12.5%). There were no clinically relevant treatment-related trends in the biochemistry, haematology, urinalysis, vital signs or ECG data. Higher ACR20 response rates were observed in patients receiving MBS2320 versus those receiving placebo at all time points and increased with time. At Week 12, ACR50 response rates with MBS2320 treatment were increased by >4-fold compared with placebo (11.6% vs 2.5%). Greater mean reductions from baseline in DAS28-CRP were also observed in patients receiving MBS2320 versus those receiving placebo at Week 12 (-18.6% vs -8.4%). DAS28-CRP responder rates were more than doubled with MBS2320 treatment compared to placebo (5% vs 14%). These changes were mirrored by improvements in tender joint counts, reduced hsCRP and improvements in Patient Reported Outcomes of pain VAS, Patients' and Clinicians' Global Assessments of Disease Activity and Patients' Global Impression of Change. Conclusion: MBS2320 was generally well tolerated for up to 12 weeks in this RA study population. Nausea was the most common TEAE, was generally mild in severity and resolved without treatment. In this population of patients with hard-to-treat, severe, active, erosive disease MBS2320 showed evidence of a clinical benefit on both ACR20 responses and DAS28-CRP. References: [1]Patel et al, Ann Rheum Dis, 78, S2, 2019, A228 Acknowledgments: Louise Jopling, Ian Anderson, Ian Gourley, Devenini Damayanthi, Disclosure of Interests: Lisa Patel Shareholder of: Istesso Ltd, Employee of: Istesso Ltd, Laurence Skillern Consultant of: Istesso Ltd, Martyn Foster Shareholder of: Istesso Ltd, Consultant of: Istesso Ltd, Andy Gray Shareholder of: Istesso Ltd, Consultant of: Istesso Ltd, Richard Leff Consultant of: Istesso Ltd, Sam Williams Shareholder of: Istesso Ltd, Employee of: Istesso Ltd